Plant traits in relation to the performance and distribution of woody species in wet and dry tropical forest types in Panama. (25th March 2013) - Brenes‐Arguedas, Tania; Roddy, Adam B.; Kursar, Thomas A.; Tjoelker, Mark
Summary Understanding the factors that limit species distributions along environmental gradients is a central question of ecology. Here, we evaluate the hypothesis that the traits that result in performance trade‐offs between habitats contribute to the turnover of woody species along a rainfall gradient in the Isthmus of Panama. We studied 24 plant species with contrasting distributions along this rainfall gradient. We measured 18 morphological and physiological traits, and three performance variables in seedlings planted in common garden experiments in two contrasting sites across the Isthmus. We found evidence for a trade‐off suggesting that better survival during the dry season corresponded to a lower growth rate in the forest understorey. This trade‐off correlated well with the distribution of the species along the rainfall gradient and was explained mostly by variation in photosynthetic capacity. While not all species fit into this trade‐off, most dry‐distribution species, which we had previously reported to have higher drought survival, were associated with higher stem hydraulic conductance and higher capacity for CO2 assimilation. Our interpretation is that this combination of traits may be associated mostly with desiccation avoidance (deep roots) or desiccation delay (deciduousness) rather than desiccation tolerance. Despite their higher photosynthetic capacity, these species had lower growth in the low‐light understorey, probably because of higher maintenance costs (dark respiration rates). Wet‐distribution species, on the other hand, had lower photosynthetic capacity and higher leaf area ratio. This strategy is typical of shade‐tolerant species and may explain their higher growth rates in the low‐light understorey. In conclusion, our results suggest that habitat associations along the rainfall gradient in the Isthmus of Panama may result in part from a trade‐off between traits that are favourable to species that avoid or delay desiccation but that otherwise limit shade tolerance. This trade‐off may limit the capacity of some dry‐distribution species to colonize wet forests.